jurnal Jurnal syekh 2024.pdf: unka jurnal - Mochsin, Syekh (Universitas Kapuas Sintang, 2024)
Abstract The problem raised in this research is the implementation of public information in the Sintang Regency Communication and Information Service. It is known that the Bureaucratic Structure is a system carried out by public bodies in accordance with their respective duties and functions and is an implementing element of the Regional Government led by the Head of Service who is under and responsible to the Regent through the Regional Secretary in accordance with their area of ​​authority. The Sintang Regency Communication and Informatics Service has the main task of carrying out government affairs in the fields of Communication and Informatics, Statistics and Coding. Disposition in implementing policies is the attitude of implementers in implementing policies. The disposition or attitude of policy implementers can be seen through understanding and deepening, the direction of the policy response, and the intensity of the policy. Human resources are important in implementing policies because if communication is going well between policy makers and implementers but there are not adequate resources then policy implementation will not run well. The conclusion of this research is that the implementation of public. Suggestions for the implementation of Public information in the Sintang Regency Communication and Informatics Service need to be pursued continuously and sustainably in facing community demands, improving Human Resources and other supporting infrastructure. Keywords: Implementation, Information, Public, Diskominfo.